Occurrence of Megamouth Shark, Megachasma pelagios (Lamniformes: Megachasmidae) in the Central Indian Ocean - Rahman, Riyas P. K.; Abhijith, E. K.; Krishnaprasad, P. H.; Sarlin, P. J.; Sureshkumar, S. (Zootaxa, 2025)
The Megamouth Shark (Megachasma pelagios), considered rare, has been observed in increased records recently, surpassing 273. The present study provides insight into the limited Indian Ocean records by reporting a specimen collected in Sakthikulangara Harbour, Kollam, Kerala, India. It highlights the need for monitoring and improved research to better understand this species in the Indian Ocean.